Medical secret as a basis of medical confidence in relation doctor-patient : a view from healthcare system of the Republic of Serbia - Denić, Dragana (Array, 2018)
The medical secret is one of the foundations of medical ethics and medical employees’ moral obligations, and it refers to the principle of not disclosing confidential information about the patient. Hippocrates considered the obligation to keep a medical secret to be the “sacred duty” of a physician. The medical secret was initially cultivated as ‘the know-how to remain silent’ (ars muta), while in the 18th century it becomes a legal duty that would be sanctioned according to the criminal law. Divulging a medical secret could thus lead to a criminal conviction, the obligation of compensation, and the responsibility in front of the court for medical employees.The main purpose of the keeping a medical secret is to protect patients’ interests, which follow from his constitutional rights to human dignity and privacy. The specific importance of a medical secret is attributed to it being a foundation of patients’ trust to medical employees, and this has an influence on the quality of administering medical care and on a better functioning of the medical system as a whole.The question is now how to secure the due respect and keeping of a medical secret in such a system, that is to say, how to revise this old-fashioned concept and adjust it to the reality? It is necessary to take a number of legal, organizational and technical steps by means of which a reasonable protection of privacy would be achieved. With respect to that, it is necessary to have a continued education in the domain of medical ethics of not only all of the medical employees, but also of data scientists and lawyers, because it is only the synergetic effort that will give the desired results.The investigated matter is primarily elaborated from the viewpoint of the Republic of Serbia healthcare system.